Antiaging effects of rice protein hydrolysates on Drosophila melanogaster. - Yue, Y.; Wang, M.; Feng, Z.; Zhu, Y.; Chen, J. (Journal of food biochemistry, 2021)
Rice protein hydrolysates (RPH) prepared by enzymatic hydrolysis have plenty of bioactive functions. Herein, we investigated the antiaging effect of RPH on Drosophila melanogaster (fruit fly) and its mechanisms. According to the results, fruit flies reared on 0.2% and 3.2% RP-supplement diet prolonged their average lifespan, 50% survival days, and the maximum lifespan, together with increasing superoxide dismutase, manganese superoxide dismutase, and catalase activity compared to those reared on basal diet. Further studies showed the lifespan extending effect of RPH was regulated by the cooperation with the intrinsic stress protection system (Nrf2/Keap1), age-related signaling pathway (TOR, S6K) and the expression of longevity genes (methuselah). In conclusion, the lifespan extending effect of RPH makes it possible to be applied in food and healthcare industry. PRACTICAL APPLICATIONS: In previous studies, rice protein hydrolysates (RPH) have been found to have strong antioxidant properties. But so far, most researches focused on the preparation, identification and in vitro antioxidant experiments of RPH, and there is still a lack of researches on its effect on the antioxidant system of fruit flies and the antiaging of fruit flies. This report showed that RPH enhanced the antioxidant system and prolonged the lifespan of Drosophila, which might help us rationally use rice peptides in functional foods.